Relative effectiveness of augmentation treatments for treatment-resistant depression: a systematic review and network meta-analysis. (17th August 2020) - Carter, Ben; Strawbridge, Rebecca; Husain, Muhammad Ishrat; Jones, Brett D. M.; Short, Roxanna; Cleare, Anthony J.; Tsapekos, Dimosthenis; Patrick, Fiona; Marwood, Lindsey; Taylor, Rachael W.; Mantingh, Tim; de Angel, Valeria; et al.
Abstract: Most interventions for treatment-resistant depression (TRD) are added as augmenters. We aimed to determine the relative effectiveness of augmentation treatments for TRD. This systematic review and network meta-analysis (NMA) sought all randomized trials of pharmacological and psychological augmentation interventions for adults meeting the most common clinical criteria for TRD. The NMA compared the intervention effectiveness of depressive symptoms for TRD augmentation. Of 36 included trials, 27 were suitable for inclusion in NMA, and no psychological trials could be included in the absence of a common comparator. Antipsychotics (13 trials), mood stabilizers (three trials), NMDA-targeting medications (five trials), and other mechanisms (3 trials) were compared against placebo. NMDA treatments were markedly superior to placebo (ES = 0.91, 95% CI 0.67 to 1.16) and head-to-head NMA suggested that NMDA therapies had the highest chance of being an effective treatment option compared to other pharmacological classes. This study provides the most comprehensive evidence of augmenters' effectiveness for TRD, and our GRADE recommendations can be used to guide guidelines to optimize treatment choices. Although conclusions are limited by paucity of, and heterogeneity between, trials as well as inconsistent reports of treatment safety. This work supports the use of NMDA-targeting medications such as ketamine.